2020
DOI: 10.3389/fcell.2020.00232
|View full text |Cite
|
Sign up to set email alerts
|

ANXA6 Contributes to Radioresistance by Promoting Autophagy via Inhibiting the PI3K/AKT/mTOR Signaling Pathway in Nasopharyngeal Carcinoma

Abstract: Radiotherapy is a conventional and effective treatment method for nasopharyngeal carcinoma (NPC), although it can fail, mainly because radioresistance results in residual or recurrent tumors. However, the mechanisms and predictive markers of NPC radioresistance are still obscure. In this study, we identified Annexin A6 (ANXA6) as a candidate radioresistance marker by using Tandem Mass Tag quantitative proteomic analysis of NPC cells and gene chip analysis of NPC clinical samples with different radiosensitiviti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…The PI3K/AKT/mTOR signaling pathway is involved in cell proliferation, growth, differentiation, and cytoskeletal reorganization in many types of cancer [39][40][41]. Our study showed that the overexpression of miR-124-3p affected tumor progression in NPC cells through the PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 58%
“…The PI3K/AKT/mTOR signaling pathway is involved in cell proliferation, growth, differentiation, and cytoskeletal reorganization in many types of cancer [39][40][41]. Our study showed that the overexpression of miR-124-3p affected tumor progression in NPC cells through the PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 58%
“…Among these seven IAGs, ANXA6 can regulate IL-2 homeostasis and sensitivity in T cells [19] and has been demonstrated that was correlated with the development of cancers, such as breast cancer and pancreatic cancer [20,21]. Chen et al showed that ANXA6 could enhance the radioresistance of nasopharyngeal carcinoma by inhibiting PI3K/AKT/mTOR signalling pathway [22]. AHNAK, a large structural scaffold protein, has been proven to be a prognostic biomarker in pancreatic ductal adenocarcinoma, glioma, as well as BC [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-493-5p suppresses colorectal cancer progression via the PI3K-Akt-FoxO3a signaling pathway (69). ANXA6 contributes to radioresistance by promoting autophagy via inhibiting the PI3K/AKT/mTOR signaling pathway in nasopharyngeal carcinoma (70). Recently, 4E-BP1 was shown to be phosphorylated by other kinases besides mTOR, and overexpression of 4E-BP1 was found in different human carcinomas (71).…”
Section: Discussionmentioning
confidence: 99%